Cloning and expression of haloacid dehalogenase gene from Bacillus cereus IndB1 - Enny Ratnaningsih; Idris Idris (Indonesian Journal of Biotechnology, 2017)
Organohalogen compounds, widely used as pesticides in agriculture and solvents in the industrial sector, cause environmental pollution and health problems due to their toxicity and persistence. Numerous studies have been conducted on the biodegradation of organohalogen compounds, with many focusing on the use of dehalogenase from bacteria. Haloacid dehalogenase is a group of enzymes that cleaves the carbon-halogen bond in halogenated aliphatic acids. In a previous study, the bcfd1 gene encoded haloacid dehalogenase from Bacillus cereus IndB1 was successfully isolated and characterized. This research aimed to create an expression system of the bcfd1 gene by subcloning this gene into pET expression vector and to overexpress the gene in Escherichia coli BL21 (DE3). In addition, the recombinant protein was characterized to gain a better understanding of the catalytic action of this enzyme. A high expression of bcfd1 was obtained by inducing the culture at OD550 0.8–1.0  using 0.01 mM IPTG as determined by SDS-PAGE. Zymogram analysis proved that the recombinant protein possessed dehalogenase activity. Bcfd1 activity toward monochloroacetic acid (MCA) showed specific activity of 37 U/mg at 30°C, pH 9. The predicted tertiary structure of Bcfd1 was estimated has conserved α/ß hydrolase folding motif for haloacid dehalogenase superfamily.